Buletin Peternakan : Pengaruh Beberapa Jenis Pakan Komersial terhadap Kinerja Produksi Kuantitatif dan Kualitatif Ayam Pedaging - septiani anggitasari sitompul, Osfar Sjofjan, Irfan Hadji Djunaidi (Peternakan UGM, 2016)
The study was aimed to investigate the effects of some kinds of commercial feed on quantitative and qualitative production performance of broiler chicken include feed intake, weight gain, feed conversion ratio, mortality, index of production (IP), income over feed cost (IOFC), percentage of carcasses, deposition of breast meat, meat cholesterol, and antibiotic residues.